THE IMPACT AND RESULTS OF MEMBERSHIP OF THE WTO ON THE EDUCATION SYSTEM - Abdullayev Akhrorjon,; Keldiboyeva Zumradkhan, (Educational Research in Universal Sciences, 2022)
The establishment of the World Trade Organization corresponds to the conclusion reached by the majority of the world's trading countries at the end of the Uruguay Round in April 1994. The WTO is responsible for managing the multilateral trading system. The WTO "General Agreement on Trade in Services" (GATS) requires member states to comply with the following basic rules: all member states enjoy the most-favoured-nation (MFN) regime equally; enterprises of other member states can enjoy equal treatment and market access in the territory of one member state with its local enterprises. The GATS includes a general agreement, an annex and a schedule of obligations. A Schedule of Commitments is a type of document that sets out the obligations that a WTO member will fulfill, or the obligations that a WTO member hopes to be freed from, under the market access and national treatment promoted in the GATS. When a WTO member country undertakes its obligations, it legally establishes market access standards and national arrangements in its schedule of obligations and no longer imposes other measures that restrict market access and national arrangements in trade in education services. .